2003
DOI: 10.1111/j.1654-1103.2003.tb02186.x
|View full text |Cite
|
Sign up to set email alerts
|

Germination ecology of the clonal herb Knautia arvensis: Regeneration strategy and geographic variation

Abstract: Abstract. We investigated germination responses and seed recruitment in the clonal grassland herb Knautia arvensis (Dipsacaceae) throughout its distributional range in Norway. Four predicted relationships between germination responses and field regeneration behaviour were tested using phytotron experiments and experimental and observational field studies. Seedlings appeared in all experimental microsites in the field, corroborating phytotron predictions that gap‐ or depth‐sensing strategies should be absent i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Seedling survival may be greatly increased if germination avoids times and places when/where mortality risks are comparatively high. This 'avoidance strategy' depends on the ability of seeds to appropriately sense and react to environmental signals that decrease the probability of encountering inadequate growth conditions following germination (Angevine & Chabot 1979;Kitajima & Fenner 2000;Vandvik & Vange 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Seedling survival may be greatly increased if germination avoids times and places when/where mortality risks are comparatively high. This 'avoidance strategy' depends on the ability of seeds to appropriately sense and react to environmental signals that decrease the probability of encountering inadequate growth conditions following germination (Angevine & Chabot 1979;Kitajima & Fenner 2000;Vandvik & Vange 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Divergence in response to differences in environmental characteristics is substantiated for many traits. Plant populations in dissimilar environments have been shown to differ in seed germination traits-such as temperature requirements (Meyer et al, 1989;Meyer and Monsen, 1991;Schutz and Milberg, 1997), light requirements (Meyer et al, 1990;Milberg and Andersson, 1998), response to wet-cold stratification (Dome, 1981;Meyer and Monsen, 1991;Cavieres and Arroyo, 2000;Vandvik and Vange, 2003) and dormancy (Meyer et al, 1989;Cavieres and Arroyo, 2000;Vandvik and Vange, 2003)-as well as growth, morphology and reproductive traits (Hickman, 1975;Antonovics and Primack, 1982;Potvin, 1986;VanTienderen andVan derToorn, 1991a, 1991b;Gurevitch, 1992a;Winn and Gross, 1993;Li et al, 1998;Joshi et al, 2001;Santamaria et al, 2003;Macel et al, 2007), phenology (Potvin, 1986;Van der Toorn, 1991a, 1991b;Winn and Gross, 1993;Li et al, 1998), reproductive allocation (Hickman, 1975(Hickman, , 1977Antonovics, 1981, 1982;Potvin, 1986) and physiology (Gurevitch, 1992b). These differences can be found not only among plant populations (see citations above) but also among individuals of the same populations growing in different microenvironments (Linhart, 1974;Waser and Price, 1985;Galen et al, 1991;…”
Section: Within-species Divergence In Plants; Existing Informationmentioning
confidence: 99%
“…Studies on intraspecific variability as a response to dissimilar environmental characteristics in arctic-alpine annuals are lacking. Most studies on among-population divergence in perennials (Potvin, 1986;Meyer et al, 1989;Meyer et al, 1990;Winn and Gross, 1993;Schiitz and Milberg, 1997;Santamaria et al, 2003;Vandvik and Vange, 2003;Macel et al, 2007; see also citations in Section 1.6), and annuals (Nagy and Rice, 1997), are from temperate regions. Studies on arctic and alpine plants have found that plants inhabiting both environments adapt mostly by evolving ecological races rather than generalist strategies.…”
Section: Main Contributions To Understandingmentioning
confidence: 99%
See 1 more Smart Citation